Length-Weight Relationship and Condition Factor of Labeobarbus altianalis along River Molo in Lake Baringo Basin - Kenya - Chemoiwa, E. J. (Africa Environmental Review Journal, 2022)
The condition of fish in an aquatic ecosystem is normally studied using the length-weight relationship because this provides allometric and isometric parameters, which informs the general wellbeing of the fish. The aim of this study, therefore, was to analyse the length-weight relationship and condition factor of Labeobarbus altianalis along River Molo in the Lake Baringo basin, Kenya. The parameters ‘a’ and ‘b’ of the length – weight relationship were estimated using the formula W=aLb. The length and weight relationships of L. altianalis samples studied were found to be highly correlated (r is equal or greater than 0.932). The ‘b’ values in the length-weight relationships of the fishes in the 7 sampled sites ranged between 1.93 and 3.2, implying that in most of the fish were exposed to poor environmental conditions hence poor growth. However, the fish in most sites exhibited positive allometric growth. Further, the relative condition factor ranged between 0.79 to 1.53, implying that the condition of the fish in most sites along R. Molo was good. Further study is recommended to cover both dry and wet seasons in order to provide sufficient data and information to inform management for sustainable exploitation and conservation of L. altianalis in River Molo.